The future implications of communicative discourse in fabrics and fashion designs - Prof. Dr. Hind Mohammed Sahab; Dr. Karar Haider Abdul Amir (Zien Journals, 2022)
The means of communication, through its discourse, contributed to linking individuals and groups to each other in different parts of the world, and was able to break the isolation of human society, The means of communication have also overcome the limitations of time and distance, It has been able, appropriately, to break through spatial boundaries, overcome time constraints, stimulate group interaction and participation, and contribute to the promotion of cultural diversity values, Communication technology has added new global means to many peoples and nations, just as it has placed new global tools in the hands of its adversaries, Where it contributed greatly to the knowledge of the cultures of peoples on the external level, In addition, means of communication have enabled support for cultural diversity efforts at the internal level, and have significantly increased opportunities to diversify sources of knowledge and information, But at the same time, communication technology has created a gap in the reality of relations between the West and the East, and between developed countries that possess that technology and developing countries that lack it, The current era has also witnessed a high speed and great development in the communication and information media technology industry, which reflected positively on the form, content, characteristics, spread, and impact capabilities of new media, The means of communication represent a fundamental window through which the human being of this age overlooks the world, through which he sees his culture, civilization, and progress, It guarantees freedom of expression for various forms of artistic, cultural, social, religious and philosophical practice and thus guarantees the right to cultural diversity.
Keywords: Semantics; future; communication speeches